Observations on distal intravascular pressure changes and cerebral blood flow after common carotid artery ligation in man - Holmes, A. E. (1971)
Studies of cerebral blood flow and distal intravascular pressure changes were studied in 11 patients at the time of common carotid artery ligation for the treatment of intracranial aneurysm. No neurological deterioration was observed while these patients were under observation. Cerebral blood flow in the ipsilateral hemisphere recovered rapidly while reduction in pressure, and in particular diminution of pulse pressure, persisted affording protection to the aneurysm.